Changing fortunes during economic transition: Low-wage persistence before and after German unification - Nicole Gürtzgen; André Nolte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper studies whether the transition from a centrally planned to a market economy offers new perspectives for those who, in economic terms, were relatively deprived under the old regime. Previous empirical research on this question has been limited by the availability of representative longitudinal micro-data that track individuals' labour market careers across different political regimes. Our study seeks to fill this research gap by looking at the transition of Eastern Germany following German Unification. Using a unique large-scale German administrative data set, we measure individuals' relative economic position by exploiting information on whether individuals were in the bottom of the pre-unification wage distribution. We then address the question of how workers' low or high-wage status determines their wage and labour market status within and across different regimes. We document strong evidence of a dynamic selection process into low-wage employment after Unification. Furthermore, consistent with a weak connection between individuals' true productivity and their pre-unification low-wage status, the extent of across regime state dependence is found to be small in magnitude and appears to vanish over time. For males, the small extent of across regime dependence is found to be most pronounced among the medium and high-skilled, suggesting the depreciation of general human capital as a potential explanation.
urn:nbn:de:bsz:180-madoc-409054
Keywords: J31; J64; P21; C33; C35; 330; Low Pay Dynamics; Economic Transition; State Dependence